ANALISIS KEBUTUHAN PASAR TENAGA KERJA SUBSEKTOR INDUSTRI PERIKLANAN DALAM KONTEKS INDUSTRI KREATIF DI KOTA SEMARANG - Budi - Prasetya; Subandi - Subandi (Politeknik Negeri Semarang, 2013)
The objective of this research are to describe market need toward diploma certificate graduates particularly for advertisement sub industry in Semarang Municipality, to describe type of works and field of business to which the graduates of marketing study program may enter, to describe job competence should be possesed by labour force who want to enter into creative industry. The approach used in this research was qualitative research . The informan exploited to be resource person are the people working in creative industry particulary working in advertisement agency in Semarang Municipality. The informan was selected by purposive randonm sampling technique. Data collection method used in this research was in depth interview and guided interview based on questionaire. Analysis tools exploited was descriptive analysis.